2019
DOI: 10.1002/cbin.11278
|View full text |Cite
|
Sign up to set email alerts
|

MTFP1 overexpression promotes the growth of oral squamous cell carcinoma by inducing ROS production

Abstract: Mitochondrial fission process 1 (MTFP1) is a novel nuclear‐encoded protein that promotes mitochondrial fission. Increasing lines of evidence indicate that increased mitochondrial fission is involved in carcinogenesis and tumor progression. However, the expression and biological effects of MTFP1 in cancer development is still unclear, especially in oral squamous cell carcinoma (OSCC). In this study, we first evaluated the expression of MTFP1 in 12‐paired OSCC tumor and peritumor tissues. We then explored the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…MTFR1 overexpression has been shown to promote mitochondrial fission (33). MTFP1 overexpression has been linked to increased ROS production and it has been shown to aid in mitochondrial recruitment of DNM1 along with MFF1 (34)(35)(36)(37). These results show a decreased expression of a significant inner membrane fission factor OPA1 and point to potential fission/fragmentation of mitochondrial networks in BCO.…”
Section: Discussionmentioning
confidence: 88%
“…MTFR1 overexpression has been shown to promote mitochondrial fission (33). MTFP1 overexpression has been linked to increased ROS production and it has been shown to aid in mitochondrial recruitment of DNM1 along with MFF1 (34)(35)(36)(37). These results show a decreased expression of a significant inner membrane fission factor OPA1 and point to potential fission/fragmentation of mitochondrial networks in BCO.…”
Section: Discussionmentioning
confidence: 88%
“…We found that MTFP1 was the top down-regulated DE mRNA. MTFP1 is a nuclear-encoded protein that promotes mitochondrial fission and is closely related to mitochondrial fission and fusion [ 21 ]. Mitochondrial fragmentation often occurs in dysfunctional mitochondria, resulting in decreased ATP production [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an urgent need to identify and develop novel effective treatment for OSCC. The occurrence and development of OSCC is a complex biological process ( 19 ), in which the overexpression of oncogenes (for example Notch1, fibroblast growth factor receptor 4 and c-myc plays an important role ( 20 , 21 ). Recently, a novel gene called tubulin tyrosine ligase like 12 (TTLL12) has demonstrated great interest.…”
Section: Introductionmentioning
confidence: 99%